Основні аспекти захисту особистої інформації в соціальних мережах - Заскальна, Анна; Химиця, Наталія (Видавництво Львівської політехніки, 2018)
The article deals with such issues as information threats and protection of personal information touching upon respective problems Ukraine is experiencing in the area.
Keywords: соціальні мережі; інформація; інформаційна безпека; медіаграмотність